Cadmium-Induced Hepatotoxicity in Mice - Prophylactic Supplementation of Quercetin Exerts Hepatoprotective Effect by Modulating PI3K/Akt/NF-kappaB Signaling Pathway - Liu, L; Zhao, Q; Huang, J; Lei, S (Physiological research, 2024)
This current study seeks to examine the pre-protective function of Quercetin in Cadmium (Cd)-induced liver damage, along with its modulation of the PI3K/Akt/NF-kappaB signaling pathway. A total of 60 male C57BL/6J mice were randomly assigned to four groups: control (C), quercetin (Q, 100 mg/kg/day), Cd (Cd, 2.5 mg/kg/day), and quercetin and Cd (Q+Cd). Before receiving Cd treatment, quercetin was administered intragastrically for 4 weeks. In the present study, liver markers, oxidative stress parameters, pro-inflammatory cytokines, liver histopathology, apoptotic markers and PI3K/Akt/NF-kappaB signaling molecules were examined. We observed that the body weight of the Cd-treated mice dramatically rise after 4 weeks of quercetin pre-administration, and the Cd concentration was significantly decreased. Liver function markers like alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), and lactate dehydrogenase (LDH) were significantly reduced in quercetin treatment in Cd-induced mice. Additionally, we observed that quercetin reduced Cd-mediated liver injury in mice by assessing the level of malondialdehyde (MDA), and the activities of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and glutathione (GSH) concentrations and the histological alterations. By monitoring tumor necrosis factor-alpha (TNF-alpha), interleukin-6 (IL-6), and interleukin-1beta (IL-1beta), quercetin successfully reduced the inflammatory cytokines that the Cd metal caused in the liver. Additionally, in the liver tissues of Cd-mediated, quercetin could enhance the expression of Bcl-2 and decrease the expression of p-Akt, p-PI3K, Bax, Caspase-9, Caspase-3, NF-kappaB. In conclusion, quercetin protects against Cd induced liver injury via several pathways, including oxidative stress, inflammation and apoptosis, and its protective effect correlates with antioxidant activity.
Keywords: Liver; Animals; quercetin; Proto-Oncogene Proteins c-akt; Antioxidants; oxidační stres; játra; kadmium; Phosphatidylinositol 3-Kinases; Cadmium; Oxidative Stress; lékové postižení jater; Mice; fosfatidylinositol-3-kinasy; signální transdukce; myši; Signal Transduction; protoonkogenní proteiny c-akt; Male; antioxidancia; Chemical and Drug Induced Liver Injury; NF-kappa B; mužské pohlaví; zvířata; Quercetin; Mice, Inbred C57BL; myši inbrední C57BL